MARKETING COMMUNICATION STRATEGY, ORGANIZATIONAL CULTURE, INNOVATIVE INDIVIDUAL CHARACTERISTICS AND ORGANIZATIONAL COMMITMENT IN IMPROVING SMALL AND MEDIUM ENTERPRISE PERFORMANCE - Muh. Husriadi; Fari Aus, Nada Kusuma, Amos (Adisam Publisher, 2026)
Abstrak This research focuses on communication strategies marketing, organizational culture, character individual innovative, and organizational commitment to improving performance of MSMEs in Kendari City, which is facing challenge competition and digitalization. This study aims to analyze influence these factors on the performance of MSMEs in general holistic. A qualitative approach was used with interviews in-depth study of MSME actors as a technique data collection. The results of the study showed that the marketing strategy digital- based, organizational culture that supports innovation, character individual innovative, and organizational commitment to contribute in a way significant in increasing performance of MSMEs. In addition, the application of digital technology in marketing strategies and new product development strengthens the competitiveness of MSMEs in the market. This study contributes empirically related to the importance of integration these factors are to support the sustainability of MSME businesses, as well as recommend strengthening policies that support digitalization and innovation in the MSME sector.